Benefits and Challenges of Integration of Information and Communication Technology in the Teaching and Learning of Mathematics: A Systematic Literature Highlights: Manfaat dan Cabaran Pengintegrasian Teknologi Maklumat dan Komunikasi dalam Pengajaran dan Pembelajaran Matematik : Sorotan Literatur Bersistematik - Mat Adam, Norlida binti; Raja Maamor Shah, Raja Noor Farah Azura binti; Adnan, Mazlini binti (Jurnal Pendidikan Bitara UPSI, 2022)
Teaching and Learning (TnL) using technology today is an increasingly popular approach among students and teachers. The integration of Information and Communication Technology (ICT) in TnL for Mathematics subjects provides advantages and challenges to students and teachers. The purpose of this systematic literature review is to identify the benefits and challenges faced by students and teachers in implementing TnL Mathematics online. A survey of the articles was made between the publication year 2017-2021 using three databases namely ERIC, Google Scholar and Research Gate. The findings show that the integration of ICT in TnL Mathematics provides many advantages to students such as TnL process becomes more interesting, fun, improve conceptual understanding, form critical and creative thinking in problem solving, maintain focus, give students the opportunity to explore and learn independently and also improving student achievement. The challenges in integrating ICT in mathematics are the lack of technological facilities, limited internet access, limited knowledge and skills of teachers and students and also the lack of online TnL materials. Infrastructure facilities and internet access need to be improved to ensure that online learning can be optimally utilized by teachers and students. Various programs and workshops need to be designed and implemented to increase the knowledge, skills and confidence of teachers and students in applying online learning.